Hepatoprotective Activity of Vitex trifolia against Carbon Tetrachloride-induced Hepatic Damage - Manjunatha, B. K. (Medknow Publications, 2008)
Aqueous and ethanol extracts of leaf of Vitex trifolia was investigated for hepatoprotective activity against carbon tetrachloride induced liver damage. To assess the hepatoprotective activity of the extracts, various biochemical parameters viz., total bilirubin, total protein, alanine transaminase, aspartate transaminase and alkaline phosphatase activities were determined. Results of the serum biochemical estimations revealed significant reduction in total bilirubin and serum marker enzymes and increase in total protein in the animals treated with ethanol and aqueous extracts. However significant rise in these serum enzymes and decrease in total protein level was noticed in CCl4 treated group indicating the hepatic damage. The hepatoprotective activity is also supported by histological studies of liver tissue. Histology of the liver tissue treated with ethanol and aqueous extracts showed normal hepatic architecture with few fatty lobules. Hence the present study revealed that Vitex trifolia could afford significant protection against CCl(4) induced hepatocellular injury.